Pseudomonas aeruginosa infection in augmented care: the molecular ecology and transmission dynamics in four large UK hospitals. (May 2021) - Halstead, F.D.; Quick, J.; Niebel, M.; Garvey, M.; Cumley, N.; Smith, R.; Neal, T.; Roberts, P.; Hardy, K.; Shabir, S.; Walker, J.T.; Hawkey, P.; et al.
Summary: Background: Pseudomonas aeruginosa is a common opportunistic pathogen and molecular typing in outbreaks has linked patient acquisition to contaminated hospital water systems. Aim: To elucidate the role of P. aeruginosa transmission rates in non-outbreak augmented care settings in the UK. Methods: Over a 16-week period, all water outlets in augmented care units of four hospitals were sampled for P. aeruginosa and clinical isolates were collected. Outlet and clinical P. aeruginosa isolates underwent whole-genome sequencing (WGS), which with epidemiological data identified acquisition from water as definite (level 1), probable (level 2), possible (level 3), and no evidence (level 4). Findings: Outlets were positive in each hospital on all three occasions: W (16%), X (2.5%), Y (0.9%) and Z (2%); and there were 51 persistently positive outlets in total. WGS identified likely transmission (at levels 1, 2 and 3) from outlets to patients in three hospitals for P. aeruginosa positive patients: W (63%), X (54.5%) and Z (26%). According to the criteria (intimate epidemiological link and no phylogenetic distance), approximately 5% of patients in the study 'definitely' acquired their P. aeruginosa from their water outlets in the intensive care unit. This study found extensive evidence of transmission from the outlet to the patients particularly in the newest hospital (W), which had the highest rate of positive outlets. Conclusions: The overall findings suggest that water outlets are the most likely source of P. aeruginosa nosocomial infections in some settings, and that widespread introduction of control measures would have a substantial impact on infections.